Knowledge, Attitude, and Perception of Anticipating 2022 Global Human Monkeypox Infection among Internal Medicine Residents at Palembang Indonesia: an Online Survey - Nelda Aprilia Salim; Indri Seta Septadina; Mega Permata; Harun Hudari (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2022)
Rapid increasing cases of Monkeypox infections in countries around the world, forcing medical professionals to be prepared to prevent it becoming the next global pandemic. We conducted the study to determine knowledge, attitude, and perception of doctors regarding preparedness for 2022 human monkeypox infection. This cross-sectional design research was conducted on 2-5 of August 2022, by circulating an online survey link to all internal medicine residents at the medical faculty of Universitas Sriwijaya, Dr. Mohammad Hoesin hospital Palembang Indonesia. The survey contained questions about the respondent's characteristics, knowledge, attitudes and perceptions about Monkeypox infection. A total of 75 residents agreed and completed the survey and were analyzed, with a mean age of 31 years, and 49 men (65.3%). Respondents’ knowledge of monkeypox is not very good. Almost all respondents knew that monkeypox was transmitted by direct contact, but only 53.4% knew that monkeypox was not transmitted airborne, 34.7% not sexually, and only 18.7% answered correctly that there was no specific therapy. The percentage who answered in doubt ranged from 20-30%. Respondents' attitudes and perceptions were quite good. Almost all equipped themselves with personal protective equipment and try to find information about monkeypox by attending seminars, downloading guidelines and reading online articles. A total of 58 people (77.3%) were willing to be vaccinated against monkeypox. Residents must increase the correct knowledge about this disease in order to be able to manage appropriately if they encounter cases of monkeypox infection.